2019
DOI: 10.1002/nau.24240
|View full text |Cite
|
Sign up to set email alerts
|

Improving the barrier function of damaged cultured urothelium using chondroitin sulfate

Abstract: Aims: To determine whether glycosaminoglycan (GAG) replenishment is able to improve recovery of a deficient urothelial barrier, chondroitin sulfate (CS) instillations were tested using an in vitro model. Porcine urothelial cells (Ucells) were terminally differentiated in culture conditions to construct a urothelial layer with a functional barrier. This layer was damaged to compromise barrier function to simulate a key characteristic of bladder pain syndrome/interstitial cystitis. The functional effect of subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…When confluency was reached, the medium was supplied with 5% fetal calf serum (FCS) and 2mM calcium chloride (Ca 2+ Cl) to induce terminal differentiation. [8] Terminal differentiation was confirmed with TEER measurements and immunofluorescence analyses.…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…When confluency was reached, the medium was supplied with 5% fetal calf serum (FCS) and 2mM calcium chloride (Ca 2+ Cl) to induce terminal differentiation. [8] Terminal differentiation was confirmed with TEER measurements and immunofluorescence analyses.…”
Section: Methodsmentioning
confidence: 73%
“…[1,2] The primary aim of GAG therapy is to improve barrier function and recovery of the chronically damaged urothelium. [8] Currently clinical research still outweighs the efforts done to investigate the physiological mechanisms behind GAG therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the effect of CS on the barrier function after induction of urothelial damage, Rozzenberg et al used terminally differentiated porcine urothelial cells, which are morphologically and functionally comparable with the same types of cells in a normal human urothelium. Treatment with CS significantly accelerated the recovery of the barrier function 7 h after acute damage with PS [ 31 ]. Rooney et al showed that high-molecular-weight HA significantly decreased TNFα- and PS-induced IL8 and IL6 production, increased sulfated GAG production, and decreased trans-epithelial permeability without altering tight junction protein expression in the HTB4 urothelial cell line [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The urothelial GAG layer has a crucial role in delivering a permeability barrier to prevent penetration of urinary toxins and pathogens into the bladder wall [ 24 , 26 ]. In multiple animal models [ 27 , 28 , 29 ] as well as in cell culture models [ 30 ], disruption of the GAG layer results in an induction of permeability that can be restored to normal impermeability by treatment with GAGs [ 31 , 32 , 33 ]. Most convincing is that digestion of chondroitin sulfate on the bladder surface with the specific enzyme chondroitinase ABC alone can induce the same degree of permeability as treatment with protamine sulfate [ 33 ].…”
Section: Diagnostic Criteria For Ic/bps?mentioning
confidence: 99%